Molecular identification of Bartonella bacilliformis in ticks collected from two species of wild mammals in Madre de Dios: Peru - Del Valle-Mendoza J. (2018)
ObjectiveTo study the presence of Bartonella bacilliformis in ticks collected from two wild mammals in Madre de Dios, Peru.ResultsA total of 110 ticks were collected. Among the 43 Amblyomma spp. extracted from the 3 Tapirus terrestris only 3 were positive for B. bacilliformis. In addition, 12 out of the 67 Rhipicephalus (Boophilus) microplus obtained from the 3 Pecari tajacu were positive for B. bacilliformis. For the first time B. bacilliformis have been detected in arthropods other than Lutzomyia spp. Further studies are required to elucidate the possible role of ticks in the spread of South American Bartonellosis.